2022
DOI: 10.3390/microorganisms10112131
|View full text |Cite
|
Sign up to set email alerts
|

New Therapeutic Options in Mild Moderate COVID-19 Outpatients

Abstract: Background: In recent years, the therapeutic options for COVID have significantly improved; however, the therapies are expensive with restricted access to drugs, and expeditious and difficult to manage at home. We investigated the effect of pidotimod in preventing hospitalization in patients with mild-moderate COVID-19. Methods: A total of 1231 patients between January and June 2021 were screened. A total of 184 patients with mild-moderate COVID-19 were enrolled and divided into two groups: group-A (97) had un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…But in our study, despite the timing of administration, the efficacy of the therapy was confirmed in obese and nonobese patients. This finding could be explained by the administration of home therapy with pidotimod and cholecalciferol 13 …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…But in our study, despite the timing of administration, the efficacy of the therapy was confirmed in obese and nonobese patients. This finding could be explained by the administration of home therapy with pidotimod and cholecalciferol 13 …”
Section: Discussionmentioning
confidence: 97%
“…This finding could be explained by the administration of home therapy with pidotimod and cholecalciferol. 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported high IgA production in the acute phase of COVID-19 and a marked decrease in IgA in the following months [ 36 , 37 ]. Because of this, drug therapies have been developed to modulate and enhance IgA production to treat SARS-CoV-2 infection [ 38 , 39 ]. On the other hand, we have previously observed IgA production for a prolonged period of at least 2 months after infection with SARS-CoV-2, but no correlation with PCC was investigated in this case [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has had a dramatic effect on the world, causing almost 7 million deaths worldwide and changing daily life. COVID-19 has many reports concerning different clinical manifestations and different risk factors and biomarkers associated with the worsening (1)(2)(3). According to a report from the end of May 2020, 1.3 million cases were reported to the United States Centers for Disease Control and Prevention (CDC), with 14% requiring hospitalization, 2% admitted to the intensive care unit (ICU), and 5% dying.…”
Section: Introductionmentioning
confidence: 99%